Pengaruh Penambahan Limbah Karbit Dan Variasi Abu Serabut Kelapa Terhadap Kuat Geser - Aprilia Getruda Rumngewur; Pebrinar Riani Sangle; Wong, Irwan Lie Keng (Paulus Civil Engineering Journal, 2025)
Recently, various ways have been developed to improve the soil conditions to increase soil stability. These soil improvements have been widely implemented and have shown positive results. In this research, researchers carried out soil improvement using carbide waste and fiber ash as additional materials. This research aims to determine the characteristics of the soil on Jl. Poros Lembang Kole Palian, Bittuang District, Tana Toraja Regency, South Sulawesi. This research was carried out using an experimental method, namely testing soil characteristics with soil mechanical testing. From the results of the soil mechanical testing obtained, the value obtained after testing the shear strength at a variation of 12% + 5% ash had three samples with an average = 0.449 kg/cm². The value for the variation of 12% carbide + 10% ash has three samples with an average = 0.585 kg/cm². The value for the variation of 12% carbide + 15% ash has three samples with an average = 0.615 kg/cm². Based on this research, it was concluded that the increase in soil shear strength values ​​with the addition of carbide waste and coconut fiber ash indicates that this addition can be used as a soil stabilization material.